Cancer and Diabetes: More than the Expected Connection - Ganesh K. Raut (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Cancer and diabetes are both common diseases that are increasing rapidly worldwide. Convincing evidence including epidemiological study demonstrated that diabetes (mainly type 2 diabetes) is firmly associated with different types of cancer including breast, pancreas, liver, colon and bladder cancers. But whether diabetes triggers cancer progression or cancer causes DM is still not well understood. Diabetes is a heterogeneous type of disease which is often characterized by abnormal glucose homeostasis and insulin resistance. Continuous exposure to hyperglycemia and elevated concentrations of circulating insulin might trigger cancer growth and progression, leading to poorer prognosis. However, there are some conflicting results were observed in subgroup analysis in mainly type 2 DM revealed no significant correlation between preexisting type 2 DM and prostate cancer-related mortality. Whereas, a meta-analysis was carried out by Lee et al. determined the incidence of death due to prostate cancer in men suffering from preexisting diabetic. Over the past several decades, cancer and DM remained co-existing illnesses and patients face unique challenges. However, treatment landscapes have changed with the targeted and immunotherapy but still new compounds used during the treatment causes hyperglycemia. Based on heterogeneity, further research needs to be undertaken to open new avenues of intervention for cancer associated diabetes.